Fault location in transmission lines using time-domain equations. - Pino, Gabriel (2018)
This thesis is a combination of the development of numerical models regarding transient simulation of transmission lines and their advantages associated with fault location methods. The transmission line models presented in this work are in time-domain, which is a new approach considering traditional methods as being the phasor and traveling wave techniques. The use of phasors for this purpose has some technical difficulties: the presence of a damped DC component, greater influence of the fault impedance and metrological equipment layout. This work deals with single-phase AC and mono polar DC transmission lines. The proposed transmission line model has three main differentials compared to the traditional Bergeron model: full distribution of linear resistance; full distribution of leakage conductance; and just one recurrence of historical values. The first point is critical for evaluation of the exponential component of transient short circuit currents. The second point refers to the inclusion of the corona effect in the transmission line modeling. The single recurrence indicated in the third topic is given by the complete resolution of the telegrapher\'s equations, so there is no need of serial composition to improve waveform accuracy. The principle of fault location method is calculating the absolute difference between fault voltages seen by the transmission line ends. This technique guarantees a lower influence of the fault impedance and its electrical parameters.